Sea Glass - "Shreve, Anita" (Abacus: London, 2002)
New Hampshire, 1929$1 (BWhen Sexton Beecher proposes to Honora Willard, she lays aside his flaws, as one might overlook a small stain on a beautifully embroidered tablecloth. But as the couple begins their new life in the house at Fortune's Rocks, their love is about to be tested to the limit. For the Wall Street Crash has as little time for dreams as it does the mill-workers at nearby Ely Falls, readying for strike whatever the consequences.s
Keywords: English-Fiction